Cryoextraction of Subacute, Adhesive and Immobile Airway Blood Clot With Short Freezing Time: A Case Report - Takashi Nishihara; Takayuki Takimoto; Eiji Sugimoto; Shojiro Minomo; Toru Arai (Respirology Case Reports)
ABSTRACT We report a rare case of a patient experiencing persistent exertional dyspnoea due to a subacute, adhesive and immobile airway blood clot following haemoptysis. Cryoextraction with short freezing times, which fragmented the clot into small pieces, proved effective, despite previous reports on acute airway blood clots recommending longer freezing times.